ANALISIS BELANJA DAN KINERJA PELAYANAN DINAS KESEHATAN KABUPATEN PADANG PARIAMAN TAHUN 2022-2024 - Fitri Cynthia Haeny (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This study aims to determine whether the Padang Pariaman Regency area has used APBD funds properly and efficiently. The results of this study are expected to provide input or evaluation to the Padang Pariaman Regency Government in order to improve Health Service Performance. This study was conducted in the 2022-2024 budget year period. The analysis technique used is the analysis of spending growth and spending efficiency ratio. The results of this study indicate that the budget growth and spending realization of the Padang Pariaman Regency Health Office increased in 2023 and decreased in 2024. The spending efficiency ratio increased from 2022 to 2024. However, there are budget fluctuations in this case when viewed in the performance of Padang Pariaman Regency health services there is a decrease in several indicators, especially in 2024.